PENGENALAN RABIES PADA SISWA SD NEGERI MEDOWO 3 MELALUI PROGRAM KOMUNIKASI, INFORMASI, DAN EDUKASI (KIE) - Dameanti, Fidi Nur Aini Eka Puji; luthfiana, Nurul; Sabila, Ahda; Nirmalasari, Na Young; Suseno, Raisa Qurrata A’yun; Erlinda, Tira (Jurnal Abdi Insani, 2024)
Rabies is a zoonotic disease that can be transmitted from animals to humans. Rabies remains a global threat, killing around 59,000 people each year, and dogs are still the main source of transmission. The presence of dogs in the community as one of the animals most often infected with rabies is a condition that must always be watched out for, one of which is in the group of children who are at highest risk of being bitten by rabid dogs. Communication, Information, and Education (CIE) is one of the strategies used in the comprehensive approach of the rabies eradication program in Indonesia. Increasing knowledge related to rabies in children can be done through CIE that is packaged attractively without reducing the content and information conveyed. CIE with the theme "Rabies; Introduction, Prevention, and Control" was given to 45 students of SDN Medowo 3, Medowo village, Kedungkandang district, Kediri regency using the fun teaching method through material presentation and educative games. Evaluation of the results of the Rabies CIE was carried out by comparing the results of the pretest and posttest that had been filled out by the students. The method of data analysis and interpretation was carried out descriptively quantitatively through the percentage of total correct and incorrect answers to the question variables that represent the content of the CIE material that has been given and the average score of the pretest and posttest results in each class and age group. The results of the evaluation of the question variables showed that there was an increase in students' understanding of rabies material from 85.6% to 92.5% and there was an increase in the average posttest results in all groups after education. Based on these results, it can be concluded that the Rabies CIE activities provided can increase elementary school students' knowledge regarding Rabies.